Praktik Kesehatan Reproduksi Perempuan Suku Asmat: Tinjauan Sosial Budaya - Yogi, Ruth; Hijjang, Pawennari; Poli, Agustina Ivonne; Numberi , Gerdha K.I. (JURNAL EKOLOGI BIROKRASI, 2025)
The high maternal and infant mortality rates among the Asmat tribe in South Papua Province are closely related to social and cultural values and norms that tend to discriminate against women and have a negative impact on their reproductive health. This study aims to examine how Asmat women construct social and cultural realities related to reproductive health and to understand the meaning of reproductive health behaviors in the context of pregnancy, childbirth, and the postpartum period. This study is expected to provide practical contributions in the form of scientific information for local governments in formulating socially and culturally based policies to reduce maternal and infant mortality rates. This study uses a qualitative approach with an ethnomethodological design to uncover the subjective meaning of individual actions in phenomena related to the reproductive health of Papuan ethnic women. Data were collected through observation, in-depth interviews, and documentation studies, then analyzed interpretively. The results of the study indicate that the reproductive health behavior of Asmat women is greatly influenced by cultural value systems in terms of superstructure, infrastructure, and ethnic preferences. Two cultural behavioral tendencies emerge: a loose and adaptive acculturative behavior toward modern health services, and a strict traditional behavior that tends to maintain slot deposit 5000 prohibitions, taboos, and local belief practices. It was found that the more relaxed and acculturated the community's health behavior, the faster the detection of risks and handling of health cases, which positively impacts the reduction in maternal and neonatal mortality rates. Conversely, behavior that is increasingly strict and traditional tends to increase delays in handling and worsen the risk of maternal and infant mortality.